Endothelial Regulator of Calcineurin 1 Promotes Barrier Integrity and Modulates Histamine-Induced Barrier Dysfunction in Anaphylaxis - Ballesteros-Martinez, Constanza; Mendez-Barbero, Nerea; Montalvo-Yuste, Alma; Jensen, Bettina M.; Gomez-Cardenosa, Aída; Klitfod, Lotte; Garrido-Arandia, María; Alvarez-Llamas, Gloria; Pastor-Vargas, Carlos; Vivanco, Fernando; Garvey, Lene Heise; Cuesta-Herranz, Javier; et al. (Frontiers in Immunology, 2017)
Anaphylaxis, the most serious and life-threatening allergic reaction, produces the release of inflammatory mediators by mast cells and basophils. Rcan1 is a negative regulator of mast-cell degranulation. The action of mediators leads to vasodilation and an increase in vascular permeability, causing great loss of intravascular volume in a short time. Nevertheless, the molecular basis remains unexplored on the vascular level. We investigated Rcan1 expression induced by histamine, platelet-activating factor, and epinephrine in primary human vein (HV)-/artery (HA)-derived endothelial cells (ECs) and human dermal microvascular endothelial cells (HMVEC-D). Vascular permeability was analyzed in vitro in human ECs with forced Rcan1 expression using Transwell migration assays and in vivo using Rcan1 knockout mice. Histamine, but neither PAF nor epinephrine, induced Rcan1-4 mRNA and protein expression in primary HV-ECs, HA-ECs, and HMVEC-D through histamine receptor 1(H1R). These effects were prevented by pharmacological inhibition of calcineurin with cyclosporine A. Moreover, intravenous histamine administration increased Rcan1 expression in lung tissues of mice undergoing experimental anaphylaxis. Functional in vitro assays showed that overexpression of Rcan1 promotes barrier integrity, suggesting a role played by this molecule in vascular permeability. Consistent with these findings, in vivo models of subcutaneous and intravenous histamine-mediated fluid extravasation showed increased response in skin, aorta, and lungs of Rcan1-deficient mice compared with wild-type animals. These findings reveal that endothelial Rcan1 is synthesized in response to histamine through a calcineurin-sensitive pathway and may reduce barrier breakdown, thus contributing to the strengthening of the endothelium and resistance to anaphylaxis. These new insights underscore its potential role as a regulator of sensitivity to anaphylaxis in humans.